Prevalence of malignant tumors among residents in Shaanxi province, 2019: a hospitalization records-based analysis - Xinlei MIAO; Guimin TANG; Lin REN; Qianke CHEGN; Jun CHEN; Song LENG (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo examine the prevalence of malignant tumors among residents in Shaanxi province in 2019. MethodsAll hospitalizations due to malignant tumors throughout 2019 were extracted from inpatient medical records of hospitals in Shaanxi povince. The International Classification of Diseases, 10th Revision (ICD-10) was used to categorize the inpatients' malignant tumors and multiple imputation method was adopted to adjust the covariates with missing data. National and provincial demographics were collected from National Bureau of Statistics and Statistics Yearbook of Shaanxi province for calculating age-adjusted prevalence rate. ResultsThe overall prevalence rate (1/100 000) of malignant tumors in the province during 2019 was 392.38; the highest regional prevalence rate was 523.68 for the residents of Tongchuan prefecture, while the lowest was 34.256 for those of Weinan prefecture; and the highest tumor-specific prevalence rate was 144.21 for digestive malignancies. In the male residents of the province, the top three prevalence rates were 187.50, 106.25, and 31.05 for malignancies of digestive organs, respiratory and intrathoracic organs, and lymphoid, hematopoietic and related tissues; in the female residents, the top three prevalence rates were 98.04, 70.60, and 67.18 for malignancies of digestive organs, breast, and female reproductive organs; the top three prevalence rates were 109.72, 58.15, and 30.13 for malignancies of digestive organs, respiratory and intrathoracic organs, and breast in the urban residents of the province, but in the rural residents, the top three prevalence rates were 194.32, 100.14, and 45.37 for malignancies of digestive organs, respiratory and intrathoracic organs, and female reproductive organs, respectively. The prevalent malignancies differed among the residents of various age groups and the age-specific prevalence rate of malignancies was the highest (62.89) for the residents aged 65 - 69 years. ConclusionAmong the residents in Shaanxi province during 2019, the overall prevalence rate of malignancies was relatively high and malignant tumor of digestive organs was the most prevalent malignancy; the prevalence rates of malignancies differed among the residents of different gender, various ages, and living in different regions; the results need to be concerned in early screening and control of malignant tumors in the province.